Clinical aspects and main forms of treatment for Fibromyalgia - Literature Review (Research, Society and Development, 2020)
Fibromyalgia is considered an incurable pathology and an idiopathic syndrome because its pathophysiology is not defined. The patient has symptoms such as chronic and generalized pain, tiredness and difficulty sleeping. It is considered frequent and its diagnosis is made by excluding other pathologies. Although there is still no effective treatment, pharmacological therapy helps patients to reduce symptoms. The purpose of this review was to analyze the pathophysiology involved in the development of fibromyalgia, as well as the pharmacological therapies, plants and medicinal compounds currently existing and studied for the treatment of this pathology, considering a period between 2009 and 2020. For that, the Scielo databases, Pubmed and Google Scholar were consulted. Thus, it can be seen that the existing pharmacological therapies mainly cover four classes of drugs, which are the antiepileptic drugs, tricyclic antidepressants, selective serotonin reuptake inhibitors (SSRIs) and noradrenaline reuptake inhibitors, in addition to muscle relaxants, benzodiazepines, analgesic anti-inflammatories and herbal medicines. Despite the several published guidelines regarding the treatment of fibromyalgia, so far there is no fully effective therapy and in view of this the need for new specific drugs for this pathology is evident.